Methodology for the accreditation of the masters of the University Hermilio Valdizán - Vargas-Roncal, Rosario (2019)
There search aimed to implement the methodology for the accreditation of the masters of the graduate school of the Universidad Nacional Hermilio Valdizan (MAMEP) under CONEAU - Peru model, which was validated with self-assessment mastery program management and planning education - UNHEVAL; this research needs a set of tools, processes, actors and actions as a Sub Stages and steps that allow de composing the model standards CONEAU specific products and facilitate the implementation of the phases of accreditation. The proposed methodology MAMEP 8-stage, sub-stage 19 and 46 actions (activities) in order to make it more dynamic an application that automates the organization of the methodology and data processing was integrated: from generating records of both surveys, management indicators and deliverables records through the preparation of the report of the Central Committee and the improvement plan sending in the draft final report. To validate carried out self-assessment of mastery of Education, Major in Management and Educational Planning with the participation of teachers, students and stakeholders eventually methodology underwent evaluation for which13 teachers were consulted who participated in the self and his views regarding its applicability given a rating of 4.3 on a scale of 0 to 5, concluding that the methodology influences on self high degree of master.